Pengaruh Kombinasi Musik Gamelan Dan Senam Lansia Terhadap Nyeri Sendi Pada Lansia Perempuan Di Wilayah Kerja Puskesmas Yosomulyo Banyuwangi Tahun 2022 - Erita Pura Apriliya; Rima Nur Khasanah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Degeneration of organs in aging causes joint inflammation in the elderly. The decrease in the hormone estrogen after women enter menopause makes women more prone to experiencing joint pain than men. The perception of joint pain in the elderly can get worse without any exercise. Alternatives that can be practiced include gymnastics and music. This study aims to determine the effect of a combination of gamelan music and elderly gymnastics on joint pain in elderly women in the working area of the Yosomulyo Banyuwangi Public Health Center in 2022. This research method is pre-experimental with One Group Pre-test Post-test Design. The sample size is 30 elderly women using a purposive sampling technique. The independent variables are gamelan music and elderly gymnastics which are given to respondents 8 times in 1 month. The dependent variable is joint pain as measured using the NRS observation sheet. Data analysis used the Wilcoxon test with SPSS 22. The results of the research on respondents before the intervention were that almost half of the respondents, 14 elderly (46.7%) experienced severe pain. After administering the intervention, half of the respondents, 15 elderly (50%) experienced mild pain. Wilcoxon test results showed Asymp. Sig = 0.000. This means that there is an effect of a combination of gamelan music and elderly gymnastics on joint pain in elderly women in the work area of the Yosomulyo Banyuwangi Health Center in 2022. With the results of this study, it is hoped that health workers can provide support to the elderly to increase their motivation to do gymnastics accompanied by gamelan music accompanied by their families or existing health cadres